Hearing Improvement after Myringoplasty in Association with the Tympanic Membrane Perforation Size - Muhammad Naseem Khan, Saeed Khan, Muhammad Tayyab Rasheed, Asghar Ullah Khan, Kamran Chaudhry, Muhammad Nadeem, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To evaluate hearing improvement following successful myringoplasty based on the degree of tympanic membrane perforation. Methods: This cross-sectional study was held in the department of ENT of Aziz Bhatti Shaheed Teaching Hospital and ENT, Head and Neck Surgery department, Pak International Medical College and Peshawar Institute of Medical Sciences (PIMS), Hayatabad Peshawar for the duration from December 2021 to November 2022. Myringoplasty procedures were performed on 80 individuals in total following thorough history-taking, clinical testing, and research. Hearing was tested both before and after the operation. A variety of tables, charts, and drawings are used to present the analysed data. Results: For minor perforations, 27.81 dB was the mean air-bone gap, 7.21 dB was the mean bone conduction threshold, and 33.40 dB was the mean air conduction threshold prior to surgery. In medium-sized perforations, 32.78 dB was the mean air-bone gap, 10.10 dB was the mean bone conduction threshold and 46.21 dB was the mean air conduction threshold prior to surgery. In the instance of a large perforation, 48.86 dB was the mean air-bone gap, 62.01 dB was the mean air conduction threshold, and 15.20 dB was the mean bone conduction threshold prior to surgery. After myringoplasty, the mean postoperative air-bone gap for medium, large and small perforations was 14.22 dB, 22.62 dB and 6.24 dB, correspondingly. Using the unpaired test, it was determined that the difference in airbone gap between minor and medium sized perforations closure was statistically significant. Conclusions: After myringoplasty of large size perforations, hearing gain is improved significantly. Myringoplasty and hearing enhancement are key words. Keywords: Myringoplasty, Hearing Improvement, Tympanic membrane perforations